Navigating the Efficacy Gap: An Exploration of Training Programs and Service Delivery Challenges in Nigeria’s Public Service - Oyelude, Olufunmilayo (NIU Journal of Humanities; Vol 8 No 3 (2023): NIU Journal of Humanities, Vol. 8 No. 3, September 2023, 2023)
Amidst persistent service delivery challenges in Nigeria's Public Service, reformative measures in the latter part of the 20th century, notably the adoption of training programs, were initiated to enhance effectiveness and efficiency. However, the anticipated improvements in service delivery remained elusive. This study delved into the nexus between Human Capital Development (HCD) interventions and their tangible impacts on service delivery, spanning the period from 2003 to 2014 within Nigeria’s Public Service. This qualitative study sought to explore the complex dynamics between Training programmes and their impact on service delivery in the Nigerian Public Service from 2003 to 2014. Drawing on interviews and document analysis, the study engaged with staff from various Ministries, Departments, and Agencies (MDAs) who had undergone training between 2003 and 2014. Findings suggested that while ASCON's training programmes contributed positively to Human Capital Development, they had not yielded the desired level of impact on service delivery. Multiple factors, such as inadequate infrastructure and role duplicity among Management Development Institutes (MDIs) appeared to limit the effectiveness of these programmes. Considering these findings, the study recommends that the Nigerian government should institute policies to make training with ASCON mandatory. Furthermore, a comprehensive Training Needs Assessment should precede any training initiatives to tailor the curriculum more closely to real-world needs. Finally, a substantial upgrade of ASCON's existing infrastructure is imperative for the betterment of future training outcomes. Keywords: Service delivery, Public Service, ASCON, HCD, Training